Immune Response Analysis of Children with Pulmonary TB Using Immuno Chromatography Test -Tuberculosis (ICT - TB) - Ariami, Pancawati; Astriani, Astriani; Inayati, Nurul; Khusuma, Ari (Jurnal Analis Medika Biosains (JAMBS), 2025)
Risk factors that increase the spread of Mycobacteria tuberculosis to family members are a history of contact with tuberculosis sufferers and overcrowding at home. If the child has family or close contact with a positive TB sufferer, screening is necessary. Close contact means children live in the same house or often meet the patient. TB testing involves taking sputum samples, but in reality officers often have difficulty taking sputum samples, especially children, so they have to carry out an immunochromatography-tuberculosis (ICT-TB) test. ICT-TB is a serological examination that functions as an alternative screening examination for children who have difficulty collecting sputum. To determine the immune response in children suffering from tuberculosis using the immunochromatography tuberculosis test (ICT-TB). This research is an analytical observational study with a cross-sectional design and uses a saturated sampling method where the entire population is sampled. Purposive sampling was then used to select samples during household visits so that a total sample of 44 samples was obtained.In a sample of 44 children suffering from pulmonary tuberculosis, all ICT-TB test results were negative. 55% of children with suspected pulmonary TB were boys and 45% were boys, the number of children with suspected TB in the 1st, 2nd, 3rd, 4th, 5th and 6th months of treatment was 4.2% and 16.7% respectively. %, 21%, 16.7 %, 33.3%, 8.3% and 18.3%. Based on observations of the children's health status, 43% were healthy and 2% were sick, and in terms of physical factors, the suspect's house had good physical environmental factors. All 44 suspected children had negative ICT-TB test results. Further research needs to be carried out using cohort studies, observing the development of children with tuberculosis over a period of ± 1 to 2 years, and studying contacts in families of non-children aged 0 to 14 years.